Biogenic synthesis of nanostructured iron compounds: applications and perspectives. Issue 3 (1st September 2013) - Seabra, Amedea B.; Haddad, Paula; Duran, Nelson
Abstract : 'Green nanotechnology' has attracted increasing attention in recent years because of the possibility to reduce and/or eliminate toxic substances. Indeed, biogenic syntheses of nanomaterials, such as nanoparticles (NPs), are considered economic and valuable alternatives for the production of metallic NPs for diverse applications. Recent studies have revealed that the development of eco‐friendly technologies in material science is under extensive investigation in the field of nanobiotechnology. Considering this scenario, this review highlights the recent advances in the biogenic syntheses of metallic iron, iron sulphides and iron oxide NPs for a wide range of applications. Moreover, this review also discusses the medical, environmental and technological applications of biogenically synthesised NPs, and the challenges to be faced to optimise the eco‐friendly production of these important nanomaterials.